Bridging the gap: inclusive practitioners in the third space and the embedding of universal design - Thomas O Shaughnessy; Tracy McAvinue (Journal of Learning Development in Higher Education)
This opinion piece considers the third space from an inclusive practice, disability, and accessibility services perspective, an area largely unexplored thus far in third space studies. Higher Education Institutions (HEIs) are becoming more responsible for accommodating an increasingly diverse student and staff population. Staff working in areas of inclusive practice are being organically drawn into the third space in a changing higher education landscape that is struggling to respond to rapidly increasing numbers, funding concerns, legislative developments, and the call for mainstreaming supports. Drawing on key research on the third space including Whitchurch (2008), McIntosh and Nutt (2022), Veles and Carter (2016), and higher education research and data from the Association for Higher Education Access and Disability (AHEAD) and the Higher Education Authority (HEA), this piece establishes the current challenges for embedding inclusive practice in higher education in Ireland. The profile and role of the inclusive practitioner in the higher education setting is especially complex; they come from varied employment and educational backgrounds and operate across academic boundaries, having gleaned expansive experience and tacit knowledge of the area. Using Homi Bhabha’s (2004) third space theory of the hybrid subject as a site for transformation as a conceptual framework, we argue that the inclusive practitioner’s hybrid, integrated, and autonomous role within the third space can bridge the gap between individual accommodations and the embedding of a whole institution approach to UDL.